Gamification on Modern Challenges for Junior High School Teachers in Teaching English Speaking Skills - Rumiati Pratiwi; Syaiful Islam (Journal of Innovative and Creativity, 2025)
This study aims to identify the modern challenges faced by junior high school teachers in teaching English speaking skills through the implementation of gamification as a method. The method used is qualitative research with a case study approach, focusing on the real experiences of teachers in the teaching context. Data were collected through in-depth interviews, classroom observations, and supporting documentation, then analyzed thematically to uncover the obstacles and strategies applied by the teachers. The results show that teachers face several challenges such as limited technological devices, limited preparation time, and difficulties in maintaining students’ interest consistently through gamification. Additionally, teachers must adjust gamification techniques to the diverse characteristics of students to make speaking learning more effective. This study contributes to the literature by providing an in-depth understanding of the practice of integrating gamification in English speaking instruction despite various obstacles, as well as highlighting specific strategies used by teachers to overcome them. Furthermore, the study offers recommendations to educational stakeholders to improve teacher training and resource provision to support the effectiveness of gamification as a tool in language learning.